208k views
1 vote
What is the formula for a^3-b^3??

User Bynx
by
4.5k points

2 Answers

0 votes

Explanation:


{(a - b)}^(3) = {(a - b)}^(2) (a - b)


{a}^(3) - 3{a}^(2) b + 3a {b}^(2) - {b}^(3) = {(a - b)}^(2) (a - b)


{a}^(3) - {b}^(3) + 3ab(a - b)= {(a - b)}^(2) (a - b)


{a}^(3) - {b}^(3)= {(a - b)}^(2) (a - b) + 3ab(a - b)


{a}^(3) - {b}^(3) = (a - b)(( {a}^(2) - 2ab + {b}^(2) ) - 3ab)


{a}^(3) - {b}^(3) = (a - b)( {a}^(2) + ab + {b}^(2) )

User Marom
by
5.7k points
5 votes

Answer:


\boxed{\mathrm{view \ explanation}}

Explanation:

The difference of two cubes formula is given as:


a^3-b^3 =(a-b)(a^2 +ab+b^2)

User ThePeter
by
4.5k points